2015
DOI: 10.1016/j.apcata.2015.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co/Ni ratios in cobalt nickel mixed oxide catalysts on methane combustion

Abstract: 2Graphical abstract Highlights 1. Co-Ni mixed oxide having the ratios of Co to Ni of (50:50) exhibits the highest activity among the known transition metal oxide catalysts.2. Co-Ni mixed oxides having the ratios of Co to Ni of (50:50) show the highest activity for methane combustion.3. Distorted NiCo2O4 spinel structure plays a key role as the active sites for methane combustion.3 Abstract A series of cobalt nickel mixed oxide catalysts with the varying ratios of Co to Ni, prepared by co-precipitation method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 62 publications
5
62
0
Order By: Relevance
“…Lim et al. investigated the effect of different components in cobalt–nickel binary catalysts on methane combustion at a relatively low concentration (1500 ppm), but the temperature of complete methane oxidation was above 500 °C . According to the references above, it is expected that cobalt–nickel mixed oxides may be ideal catalysts for lean methane oxidation; however, lowering the temperature for catalytic combustion of methane is still a main issue.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lim et al. investigated the effect of different components in cobalt–nickel binary catalysts on methane combustion at a relatively low concentration (1500 ppm), but the temperature of complete methane oxidation was above 500 °C . According to the references above, it is expected that cobalt–nickel mixed oxides may be ideal catalysts for lean methane oxidation; however, lowering the temperature for catalytic combustion of methane is still a main issue.…”
Section: Introductionsupporting
confidence: 90%
“…With respect to the pore volume, Co1Ni4 had the smallest pore volume of 0.0821 cm 3 g −1 . When it comes to the average pore size, we found a phenomenon similar to the surface area, that is, the pure single oxides (Co0Ni10, Co10Ni0) have higher average pore size than the cobalt–nickel mixed oxides, indicating that the two pure single oxides have similar physical properties in some respects …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 2a, there were three distinct reduction peaks in NiCo 2 O 4 , and the peaks appeared at 253 and 360 °C, corresponding to the reduction steps of Co 3+ to Co 2+ and Co 2+ to Co 0 , respectively (Gou et al 2013; Lim et al 2015), while the peak appeared at 315 °C, which was attributed to the reduction of Ni 2+ to Ni 0 . However, in comparison to NiCo 2 O 4 , the H 2 -TPR profile of the NiCo 1.95 Pd 0.05 O 4 catalyst showed one slight peak and one strong broad peak.…”
Section: Resultsmentioning
confidence: 99%
“…Materials with exposed (110) planes show enhanced catalytic activity for methane oxidation compared with those only exposing (100) or (111) facets, enabling complete methane conversion below 400 °C (GHSV = 40 000 mL g −1 h −1 ) . Bimetallic NiCo 2 O 4 has been shown to have better catalytic activity than any single metal oxide due to structural disorder, making this a particularly enticing candidate for catalysis, as well as energy conversion and storage applications . The effect of the Ni/Co ratio in nickel cobalt oxides on methane oxidation has been investigated and it was found that distorted NiCo 2 O 4 spinel catalysts show excellent activity with 90% conversion at ≈470 °C (GHSV = 60 000 mL g −1 h −1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic NiCo 2 O 4 has been shown to have better catalytic activity than any single metal oxide due to structural disorder, making this a particularly enticing candidate for catalysis, as well as energy conversion and storage applications . The effect of the Ni/Co ratio in nickel cobalt oxides on methane oxidation has been investigated and it was found that distorted NiCo 2 O 4 spinel catalysts show excellent activity with 90% conversion at ≈470 °C (GHSV = 60 000 mL g −1 h −1 ) . Trivedi et al developed NiCo 2 O 4−δ spinel catalysts by reactive calcination of precursors in a CO‐air environment to expose more active sites.…”
Section: Introductionmentioning
confidence: 99%